Identification of a small molecule inhibitor that stalls splicing at an early step of spliceosome activation - Sidarovich, Anzhalika (eLife, 2017)
Small molecule inhibitors of pre-mRNA splicing are important tools for identifying new spliceosome assembly intermediates, allowing a finer dissection of spliceosome dynamics and function. Here, we identified a small molecule that inhibits human pre-mRNA splicing at an intermediate stage during conversion of pre-catalytic spliceosomal B complexes into activated B(act) complexes. Characterization of the stalled complexes (designated B(028)) revealed that U4/U6 snRNP proteins are released during activation before the U6 Lsm and B-specific proteins, and before recruitment and/or stable incorporation of Prp19/CDC5L complex and other B(act) complex proteins. The U2/U6 RNA network in B(028) complexes differs from that of the B(act) complex, consistent with the idea that the catalytic RNA core forms stepwise during the B to B(act) transition and is likely stabilized by the Prp19/CDC5L complex and related proteins. Taken together, our data provide new insights into the RNP rearrangements and extensive exchange of proteins that occurs during spliceosome activation. DOI: http://dx.doi.org/10.7554/eLife.23533.001